Comparative immunohistochemical characteristic of expression levels of Ki-67, p53, caspase 3 in non-invasive and invasive intestinal-type gastric adenocarcinoma - V. A. Tumanskiy; T. A. Khrystenko (Zaporozhye State Medical University, 2016)
Aim. Comparison analysis of expression levels of Ki-67, p53, and caspase 3 was performed between the tumor cells and the stromal cells of non-invasive intestinal-type gastric adenocarcinoma on the one hand and the tumor cells and the stromal cells of invasive intestinal-type gastric adenocarcinoma on the other hand. Materials and methods. For this purpose, pathohistological and immunohistochemical studies were used. The surgical material of 10 patients with non-invasive (pTis, pT1) intestinal-type gastric adenocarcinoma and 10 patients with invasive (pT2, pT3, pT4) intestinal-type gastric adenocarcinoma were analyzed. Results. It was established that intestinal-type gastric adenocarcinoma is characterized by the medium Ki-67 labeling index, the low expression level of p53, the low expression level of caspase 3 in the tumor cells, and also the low Ki-67 labeling index and the extremely low expression level of caspase 3 in the stromal cells. The tumor cells of invasive intestinal-type gastric adenocarcinoma are characterized by the 2 times higher expression level of p53, than the tumor cells of non-invasive intestinal-type gastric adenocarcinoma. Moreover, direct correlation between the medium Ki-67 labeling index of the tumor cells and the low Ki-67 labeling index of the stromal cells, and also direct correlation between the medium Ki-67 labeling index in the tumor cells of intestinal-type gastric adenocarcinoma and the low expression level of p53 in these cells were identified. Conclusions. These data demonstrate a significantly more activity of proliferation and apoptosis in the tumor cells of intestinal-type gastric adenocarcinoma, in comparison with the stromal cells of this tumor. Invasive intestinal-type gastric adenocarcinoma differs by the 2 times higher expression level of p53, in comparison with the same index for non-invasive carcinoma. Furthermore, a tight association between proliferative processes in the tumor cells and in the stromal cells of intestinal-type gastric adenocarcinoma, and also an association between proliferative processes and accumulation of mutant protein p53 in the tumor cells of intestinal-type gastric adenocarcinoma were identified.